Relasi Musikal Antara Pemusik dengan Penonton Parkiran Jazz di Surakarta - Christianata, Fabianus Deny (TAMUMATRA, 2023)
This research was conducted in Surakarta, precisely at a jazz music event called Parkiran Jazz. This study aims to find out what are the background of the formation of musical relations between musicians and the audience. The research method used is a qualitative method with an ethnographic approach. The process of collecting data is done through document studies, field observations, audio visual recordings, and interviews. The focus of the problem in this study is why musical relations between musicians and audiences can form in jazz performances at the Jazz Parkiran event. In the discussion of this research, the analysis applied is the concept of proxemic relations from KeirEllam case studies of theater and drama performances. This proxemic relational concept consists of three analytical perspectives, namely the issue of taste, show momentum, and the distance or level of the actor's stage with the audience. Through these three perspectives of analysis the researcher sees a great influence in forming emotional relations between actors with the audience. After applying the jazz performance problems, the three perspectives of the analysis are relevant and represent all forms of events capable of building a strong musical relationship between the musician and the audience. Based on the results of the analysis in the discussion it can be concluded that the issue of song tastes, show momentum, and stage distance between the musician and the audience are factors that have a major influence on the formation of the musical's musical relationship with the Jazz Parkiran audience in Surakarta